Impact of cannabis use in patients with implantable cardiac defibrillators admitted with acute heart failure: a national perspective. (3rd October 2022) - Mathew, D; Hasin, F; Bumrah, K; Kosuru, B; Singh, V; Bedi, P
Abstract: Background: Cannabis is the most popular recreational drug in the United States but knowledge about its health implications remain limited. Cannabis use has been linked to acute myocardial infarction and congestive heart failure. The effect of cannabis use in acute decompensated heart failure in patients with Implantable Cardiac Defibrillators (ICDs) is not known. Objective: In this study, we sought to explore the impact of cannabis use in patients with Implantable Cardiac Defibrillators (ICDs) admitted with acute decompensated heart failure. Methods: We queried the 2019 National Inpatient Sample (NIS) database for all patients aged ≥18 with ICD devices admitted with acute heart failure. Patients were stratified into two groups based on Cannabis use. We excluded patients with opioid, amphetamine, psychostimulants, cocaine, sedative, and hallucinogen abuse disorders to eliminate the effect of polysubstance use. Results: Of the 174, 295 hospitalization events for acute decompensated heart failure with ICDs, 1824 were noted to have diagnosis of cannabis use (CU). Patients with CU were younger (mean age 52.4y vs 68.5y) and mostly male (81.1% vs 18.9%). CU group had lower prevalence rates for anemia, atrial fibrillation, coronary artery disease, diabetes, cirrhosis, chronic kidney disease and hypothyroidism. They had higher rates of alcoholism, tobacco use and depression. The primary outcome studied was inpatient mortality. Secondary outcomes include cardiac arrest, myocardial infarction, cardiogenic shock, ventricular tachycardia, ventricular fibrillation, stroke, respiratory failure, pleural effusion, acute kidney injury, length of stay (LoS) and hospital charges. Patients in CU group were noted to have decreased length of stay (reduction in adjusted mean LoS: 2.14 days, P=0.000), mortality (adjusted OR: 0.14, P=0.006) and respiratory failure (adjusted OR: 0.53, P=0.009). Conclusion: Among patients with implantable cardiac defibrillator admitted for acute decompensated heart failure, cannabis users were younger and mostly male. These patients were noted to have decreased length of stay, inpatient mortality, and respiratory failure. Funding Acknowledgement: Type of funding sources: None.